Sahel Visions : Planned Settlement and River Blindness Control in Burkina Faso - McMillan, Della E. (Book collections on Project MUSE., 1995)
When an international health initiative succeeded in wiping out onchocerciasis (river blindness) in Burkina Faso (previously Upper Volta), it allowed the settlement of the sparsely populated Volta Valley by the Mossi people - a development plan by which the Burkinabe government sought to relieve population pressure, establish communities, and increase cotton production. Anthropologist Della McMillan followed this visionary plan over twelve years as people relocated communities, founded farms, dealt with officials, entered the market, and in some instances moved on. Sahel Visions examines familiar themes of development - land tenure, technological change, government pricing - as issues that affected people's daily lives. Over the years, certain settler households became highly successful; others improved their living standards but lacked the management skills to excel; still others acquired an entrepreneurial motivation and relocated to a new area where there were better opportunities to develop trade and agricultural enterprises. McMillan's longitudinal study examines the question of how development occurs or fails to occur, and it offers unusual insight into how visions of progress - held by developers, settlers, and even researchers - originate and are revised. As a case study, Sahel Visions synthesizes much other work on this well-known project and offers sensible recommendations to planners for diversified production systems of crops, livestock, and nonfarm employment. In addition to providing a touchstone for similar endeavors, it brings the concepts of ecological anthropology to the study of economic development in the Third World.